2017
DOI: 10.1016/j.jebo.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

How do police use race in traffic stops and searches? Tests based on observability of race

Abstract: When a police officer decides whether to initiate a traffic stop, the driver's race is less likely to be known during darkness, but always observed after the stop takes place. If officers use information optimally, this flow of information about race leads to specific empirical predictions, which are tested using data on traffic stops in Minneapolis. The prediction about stops is supported, but those concerning searches are not. This pattern of results implies that police choices were inconsistent, which is ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…First, VOD cannot account for the potential impact of vehicle profiling on disproportionality. Ritter (2017) has suggested that police officers may be more likely to stop drivers of vehicles that are more commonly associated with minority individuals at night. However, this hypothesis has not been validated empirically and we were not able to assess this with our data.…”
Section: Discussionmentioning
confidence: 99%
“…First, VOD cannot account for the potential impact of vehicle profiling on disproportionality. Ritter (2017) has suggested that police officers may be more likely to stop drivers of vehicles that are more commonly associated with minority individuals at night. However, this hypothesis has not been validated empirically and we were not able to assess this with our data.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is that there may be discrimination in the determination of fault for an accident as discussed in West (2018). 10 As of writing and to the authors knowledge, applications of the test include Grogger and Ridgeway (2006) in Oakland, CA; Ridgeway (2009) Cincinnati, OH; Ritter and Bael (2009) and Ritter (2017) in Minneapolis, MN;Wheeler (2010, 2012) as well as Horace and Rohlin (2016) in Syracuse, NY; Renauer, Henning, and Covelli (2009) in Portland, OR; Taniguchi et al (2016aTaniguchi et al ( , 2016bTaniguchi et al ( , 2016cTaniguchi et al ( , 2016d in Durham Greensboro, Raleigh, and Fayetteville, North Carolina; Masher 2016 Ross, Fazzalaro, Barone, and Kalinowski (2015, 2016, 2017a, 2017b, 2018 in Connecticut and Rhode Island, Racial & Identity Profiling Advisory Board (2020) in California, and Sanchagrin et al (2019) in Oregon. from the statistics, computer science, and economics literatures to real world problems.…”
Section: E N D N O T E Smentioning
confidence: 99%
“…As of writing and to the authors knowledge, applications of the test include Grogger and Ridgeway (2006) in Oakland, CA; Ridgeway (2009) Cincinnati, OH; Ritter and Bael (2009) and Ritter (2017) in Minneapolis, MN; Worden, McLean, and Wheeler (2010, 2012) as well as Horace and Rohlin (2016) in Syracuse, NY; Renauer, Henning, and Covelli (2009) in Portland, OR; Taniguchi et al. (2016a, 2016b, 2016c, 2016d) in Durham Greensboro, Raleigh, and Fayetteville, North Carolina; Masher (2016) in New Orleans, LA; Chanin et al.…”
mentioning
confidence: 99%
“…There is an extensive literature that examines disparities in police treatment based on race. African American and Latino individuals are more often stopped by police in traffic stops and more likely to be searched when stopped (for example, Anwar & Fang, 2006;Gelman, Fagan, & Kiss, 2007;Gross & Barnes, 2002;Knowles, Persico, & Todd, 2001;Pierson et al, 2017;Ritter, 2017). They are also more likely to be stopped by police in stop-and-frisk interactions (Coviello & Persico, 2015;Ridgeway, 2007) and to be arrested (Bailey, 2014).…”
Section: Disparities In Police Stops and Their Effectsmentioning
confidence: 99%